Faktor Yang Berhubungan Dengan Pencegahan Kekambuhan Hipertensi Pada Penderita Hipertensi Di Wilayah Kerja Puskesmas Wua Wua Tahun 2023 - Siti Masita Zahra Ohoira; Harleli Harleli; Siti Nurfadilah H (Pusat Riset dan Inovasi Nasional, 2024)
Recurrent hypertension is a repeated increase in high blood pressure above 140/90 mmHg. Factors that can cause a recurrence of high blood pressure include: consuming unhealthy foods, consuming caffeine and smoking, rarely exercising, not maintaining body weight, consuming fatty foods, consuming foods high in fat and consuming unlimited alcohol. To prevent the recurrence of high blood pressure, patients should keep the following in mind: Get enough rest, change to a healthy diet, exercise, avoid alcohol, avoid stress, and handle the daily workload. The capacity to manage oneself and be positive, such as managing emotional intensity and reactivity, is important for preventing recurrence of hypertension and managing blood pressure. The aim of this study is to identify factors related to the prevention of hypertension recurrence in hypertensive patients. This type of research involves observational analysis with a cross-sectional research design. The study population consisted of 71 hypertensive patients who lived in the Wua Wua Community Health Center working area. The research results show the value of P = 0.263 < a = 0.05. This means that knowledge about high blood pressure and recurrence prevention is irrelevant. The research results show a value of P = 0.002< a = 0.05. This means that there is a link between treating hypertension and preventing recurrence. The research was conducted for 61 days.